Physiological responses and predictors of performance in a simulated competitive ski mountaineering race - Lasshofer, M.; Seifert, J.; Wörndle, A.-M.; Stöggl, T. (Journal of Sports Science & Medicine, 2021)
Competitive ski mountaineering (SKIMO) has achieved great popularity within the past years. However, knowledge about the predictors of performance and physiological response to SKIMO racing is limited. Therefore, 21 male SKIMO athletes split into two performance groups (elite: VO2max 71.2 ± 6.8 mlxmin-1/ kg-1 vs. sub-elite: 62.5 ± 4.7 mlx min-1x kg-1) were tested and analysed during a vertical SKIMO race simulation (523 m elevation gain) and in a laboratory SKIMO specific ramp test. In both cases, ox ygen consumption (VO2), heart rate (HR), blood lactate and cycle characteristics were measured. During the race simulation, the elite athletes were approximately 5 min faster compared with the sub-elite (27:15 ± 1:16 min; 32:31 ± 2:13 min; p < 0.001). VO2 was higher for elite athletes during the race simulation (p = 0.046) and in the laboratory test at ventilatory threshold 2 (p = 0.005) and at maximum VO2 (p = 0.003). Laboratory maximum power output is displayed as treadmill speed and was higher for elite than sub-elite athletes (7.4 ± 0.3 km h-1; 6.6 ± 0.3 km h-1; p < 0.001). Lactate values were higher in the laboratory maximum ramp test than in the race simulation (p < 0.001). Pearson´s cor relation coefficient between race time and performance parame ters was highest for velocity and VO2 related parameters during the laboratory test (r > 0.6). Elite athletes showed their superiority in the race simulation as well as during the maximum ramp test. While HR analysis revealed a similar strain to both cohorts in both tests, the superiority can be explainable by higher VO2 and power output. To further push the performance of SKIMO ath letes, the development of named factors like power output at maximum and ventilatory threshold 2 seems crucial.